Case Report: Deep and durable response to talazoparib in germline BRCA2-mutated rectal neuroendocrine carcinoma - Khealani, Milan; Park, Byoung Uk; Schat, Robben; Antonarakis, Emmanuel S.; Gupta, Arjun (Frontiers in Oncology, 2025)
High-grade neuroendocrine carcinoma (NEC) of the rectum is a rare and aggressive malignancy, with limited treatment options and a poor prognosis. We report the successful off-label use of the PARP inhibitor talazoparib in a patient with metastatic, germline BRCA2-mutated rectal NEC who had a contraindication to standard immunotherapy due to underlying autoimmune disease. A 55-year-old man with ongoing severe psoriatic arthritis presented with a two-week history of rectal pain, abdominal distention, and diarrhea. Cross-sectional imaging demonstrated a rectal mass with mesorectal lymphadenopathy and multiple liver metastases. Biopsy of the rectal lesion demonstrated a high-grade, poorly differentiated NEC with a Ki-67 proliferation index of 99%. Comprehensive tumor molecular profiling identified a pathogenic BRCA2 mutation (c.5291C>G; p.Ser1764*, with loss of the wild-type allele), which was confirmed to be a germline alteration through germline testing. There were also biallelic inactivations of APC, TP53, and RB1. The patient received four cycles of induction chemotherapy with carboplatin and etoposide, achieving a partial radiographic response; however, treatment was complicated by cytopenias and significant fatigue. Immunotherapy was considered inappropriate as part of his initial systemic therapy regimen or as maintenance treatment due to the severe underlying autoimmune condition. Based on the germline BRCA2-mutated (gBRCA) status, we requested emergency approval for off-label use of talazoparib, a poly(ADP ribose) polymerase (PARP) inhibitor. At 12.5 months from initial diagnosis, including after 7.5 months on talazoparib, the patient continues to show ongoing radiographic response with excellent tolerability and no adverse effects. This case illustrates the potential role of PARP inhibitors in the management of BRCA2-mutated high-grade rectal NEC. Molecular profiling techniques may uncover actionable genetic targets in rare, aggressive cancers without standard treatment options or in patients with co-morbidities that preclude standard treatment regimens.